Impact of gene polymorphisms of interleukin-18, transforming growth factor-β, and vascular endothelial growth factor on development of IgA nephropathy and thin glomerular basement membrane disease - Hee-Yeon Jung; Jang-Hee Cho; Jeong-Hoon Lim; Chung-Hoon Yu; Ji-Young Choi; Se-Hee Yoon; Sun-Hee Park; Yong-Lim Kim; Chan-Duck Kim (The Korean Society of Nephrology, 2012)
Background: We investigated the effects of gene polymorphisms on the development of IgA nephropathy and thin glomerular basement membrane (GBM) disease by analyzing polymorphisms in the interleukin (IL)-18, transforming growth factor (TGF)-β, and vascular endothelial growth factor (VEGF) genes in Korean patients. Methods: This study included 146 normal individuals and 69 biopsy-proven IgA nephropathy and 44 thin GBM disease patients. The gene polymorphisms −607 A/C and −137 G/C in IL-18, −509C/T and T869C in TGF-β, and −2578C/A and 405C/G in VEGF were investigated in DNA extracted from peripheral blood. Results: The frequencies of the IL-18 −607CC genotype (43.5% vs. 21.2%, P=0.002, P corrected=0.012) and the VEGF 405 GG genotype (37.7% vs. 21.2%, P=0.002, P corrected=0.012) were significantly increased in the IgA nephropathy group compared with the control group, whereas no significant differences in genotype frequency were observed between the thin GBM disease and control groups. However, there were no significant differences in genotype and allele frequencies between the IgA nephropathy and thin GBM disease groups. Conclusion: This study did not show any statistically significant differences of six selected gene polymorphisms of the IL-18, TGF-β, and VEGF genes between IgA nephropathy and thin GBM disease. Additional extensive studies are required to clarify the potential role of gene polymorphism to discriminate IgA nephropathy and thin GBM disease without renal biopsy.